2005
DOI: 10.7202/705419ar
|View full text |Cite
|
Sign up to set email alerts
|

Application des techniques physiques, géochimiques et isotopiques pour l'évaluation de l'infiltration sous climat tempéré

Abstract: Depuis plusieurs années, la Zone Non Saturée d'une parcelle expérimentale au nord de l'Italie (plaine du Pô) a fait l'objet de nombreuses études sur les caractéristiques physiques et géologiques du milieu, ainsi que sur les modalités du mouvement des eaux d'infiltration. Le site a été équipé de 6 tensiomètres à mercure, 6 bougies poreuses pour l'échantillonnage de l'eau et d'un tube d'accès pour la sonde à neutrons.L'application des différentes méthodes d'évaluation a fourni, pour la période d'étude (Septembre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The local recharge is related to surface water, such as that of the Dora Baltea River, and several artificial canals in the investigated area; the precipitation effect is instead rather negligible. Adorni-Braccesi et al (2001) studied the indirect infiltration of the rainfall, comparing physical methods and geochemical approaches, and found that locally the groundwater recharge is due more to the lateral recharge from the river than to the vertical recharge due to rainfall. The precipitations influence the surface water flow at a regional level and indirectly influence the groundwater recharge.…”
Section: Geological and Hydrogeological Frameworkmentioning
confidence: 99%
“…The local recharge is related to surface water, such as that of the Dora Baltea River, and several artificial canals in the investigated area; the precipitation effect is instead rather negligible. Adorni-Braccesi et al (2001) studied the indirect infiltration of the rainfall, comparing physical methods and geochemical approaches, and found that locally the groundwater recharge is due more to the lateral recharge from the river than to the vertical recharge due to rainfall. The precipitations influence the surface water flow at a regional level and indirectly influence the groundwater recharge.…”
Section: Geological and Hydrogeological Frameworkmentioning
confidence: 99%
“…As far as the direct recharge of precipitation through unsaturated zone is concerned, it was assumed from previous studies of flood plains near mountain chains, in temperate areas that the groundwater recharge, from a quantitative point of view, is due more to the lateral recharge by means of the river, than to the direct infiltration of precipitation, as shown by isotope techniques (Aranyossy et al, 1998). In the studied site, investigations on the direct infiltration of precipitation, using a comparison between physical methods and geochemical approaches have confirmed this hypothesis (Adorni-Braccesi et al, 2001).…”
Section: Step 1: Geological and Hydrogeological Features Of The Sitementioning
confidence: 51%